Спектроскопія плазми лазерно-індукованого пробою як метод для випробовування і моделювання нерівноважної плазми у фізиці високих енергій - Gomidze, N.; Jakobia, D.; Khajidhvili, M.; Kalandadze, L.; Jabnidze, I.; Makharadze, K.; Nakashidze, O.; Shainidze, J. (Publishing house "Academperiodika", 2026)
Laser-induced breakdown spectroscopy (LIBS) enables rapid elemental analysis and plasma diagnostics but suffers from limited quantitative accuracy due to the strong spatiotemporal nonuniformity of the laser-induced plasma and stochastic fluctuations in ionization-recombination kinetics. In this work, we develop and experimentally validate a deterministic–stochastic framework that couples classical rate equations with stochastic differential terms to capture shot-toshot plasma variability. The model, implemented through a first-order Runge–Kutta (RK1) scheme augmented by the Euler–Maruyama method, is quantitatively related to standard LIBS diagnostics: Stark broadening for electron density (ne), the LTE Saha equation for ionization balance, and Boltzmann plots for excitation temperature (Texc). Single-shot LIBS experiments using a 1064 nm, 7 ns Nd : YAG laser were performed on six metals (Al, Cu, brass, Pb, stainless steel, and Ti) under identical conditions. The measured spectra showed high reproducibility (intensity scatter <7%), and the extracted plasma parameters revealed consistent materialdependent trends: Al and stainless steel exhibited the highest ne (up to (7–9) × 1018 cm−3), whereas Cu and brass showed lower values (∼(2–3) × 1018 cm−3). Electron temperatures derived from the Saha equation reached 12–13 kK for high-ionization materials and <11 kK for low-ionization ones. The introduction of a stochastic fluctuation term (σ ≈ 0.05) reproduced the observed intensity scatter and improved agreement between modeled and experimental spectra. The proposed framework enhances LIBS diagnostic accuracy under transient, nonequilibrium conditions and provides a compact laboratory analogue for studying fluctuationdriven plasma dynamics relevant to high-energy-density physics, laser–plasma interactions, and fusion environments. This unified deterministic–stochastic treatment bridges applied laser spectroscopy with the broader physics of non-LTE plasmas.